Effectiveness of a web-based screening and brief intervention with weekly text-message-initiated individualised prompts for reducing risky alcohol use among teenagers: study protocol of a randomised controlled trial within the ProHEAD consortium - Diestelkamp, Silke; Kaess, Michael; Bauer, Stephanie; Salize, Hans Joachim; Moessner, Markus (Trials, 2019)
Early and excessive alcohol use is a significant threat to healthy development. Evidence supports the effectiveness of electronic alcohol interventions for young drinkers. However, effects are typically small and studies targeting under 18-year-olds are scarce. This trial is the first to evaluate the effectiveness of a single-session, brief, motivational, web-based intervention (ProWISE) plus weekly text-message-initiated individualised prompts (TIPs) in reducing alcohol consumption and alcohol-related harm among children and adolescents aged ≥ 12 years. TIPs are designed to decrease risky alcohol use by reaching youth in the contexts of their everyday lives and by providing individualised feedback on drinking intentions, actual drinking and succession in achieving personal goals for low-risk drinking or abstinence.